Dietary Tomato Varieties Similarly Inhibit Prostate Carcinogenesis in the TRAMP Model in Association with Distinct Transcriptomic and Metabolomic Profiles. (29th May 2020) - Geraghty, Connor; Thomas-Ahner, Jennifer; Powell, Remy; Schmidt, Nathan; Chitchumroonchokchai, Chureeporn; Riedl, Ken; Solden, Lindsey; Bailey, Michael; Hussan, Hisham; Francis, David; Cooperstone, Jessica; Mo, Xiaokui; et al.
Abstract: Objectives: Lycopene intake is associated with reduced risk of prostate cancer, especially lethal disease. Tangerine tomatoes contain highly bioavailable lycopene isomers, compared to red tomatoes, but impact of isomers on cancer preventive bioactivity are unknown. Our goals are: (1) to determine if feeding tomato containing diets with differing lycopene isomers inhibit transgenic adenocarcinoma of the mouse prostate (TRAMP) carcinogenesis, and (2) to determine key early metabolic and transcriptional pathways through which tomatoes act to prevent carcinogenesis. Methods: We examine prostate carcinogenesis in the TRAMP model, comparing two tomatoes with distinct lycopene isomer profiles: all- trans -lycopene-rich red tomatoes and cis -lycopene-isomer-rich tangerine tomatoes. Weanling TRAMP and wild type (WT) mice were fed AIN-93 G control, 10% tangerine tomato + AIN-93 G (w/w), or 10% red tomato + AIN-93 G (w/w) diet until 10 or 18 wks. At 10 wks., prostate RNA-seq and plasma metabolomics were performed on TRAMP and WT samples. At 18 wks., plasma carotenoid analysis and histopathology was performed on TRAMP mice. Results: At 18 wks., plasma lycopene concentrations were 2.84-fold greater in tangerine tomato-fed mice than red tomato-fed mice (p < 0.0001), yet both red and tangerine tomato diets similarly prevent carcinoma incidence compared to the control diet by 43% and 36% respectively (p < 0.001, both vs. control). Our investigation of early carcinogenesis (10 wks.) shows that both tomato diets similarly impact the plasma metabolome, and we define prostate transcriptomic profiles mediated by TRAMP genotype, such as inflammation- and immune-regulated pathways, that are inhibited by dietary tomato. We identify an inflammatory gene panel (Olr1, Il1a, Cscl9, and Ccl22) which is inhibited by tomato diets. In a human prostate cancer database, higher expression of this gene panel is associated with a more aggressive phenotype. Conclusions: Together, our results implicate red and tangerine tomatoes as potentially beneficial for the inhibition of early prostate carcinogenesis through the modulation of transcriptional programs centered on inflammation and the immune response. Our findings support efforts to test novel tomato products for the inhibition of human prostate carcinogenesis. Funding Sources: AICR, NIH P30, USDA NNF.